Corruption Prevention Efforts Against Investment: Empirical Evidence in West Nusa Tenggara Province: Upaya Pencegahan Korupsi Terhadap Investasi: Sebuah Bukti Empiris Di Provinsi Nusa Tenggara Barat - Almakkiyah, Munajah (Academia Open, 2026)
General Background: Investment plays a crucial role in regional economic growth through increased production capacity and job creation. Specific Background: In West Nusa Tenggara Province, investment realization remains uneven across districts despite strengthened corruption prevention efforts through the Monitoring Center for Prevention (MCP). Knowledge Gap: Previous studies provide inconsistent findings and rarely examine subnational contexts while incorporating structural factors such as agglomeration, human capital, and labor force participation. Aims: This study analyzes the relationship between corruption prevention and regional investment while controlling for agglomeration, human capital, and labor force participation. Results: Using balanced panel data of 10 districts/cities during 2019–2024 and panel regression analysis, the findings reveal that corruption prevention does not show a linear relationship with investment but exhibits a positive and significant nonlinear effect, indicating a threshold consistency pattern. Agglomeration, human capital, and labor force participation also show positive and significant relationships with investment. Novelty: This study introduces MCP as a proxy for corruption prevention at the district/city level and demonstrates a nonlinear threshold relationship between governance reform and investment. Implications: The findings highlight the importance of consistent institutional reform, improved licensing services, strengthened economic agglomeration, and workforce quality development to support sustainable regional investment. Highlights• Nonlinear pattern shows governance reform requires sustained consistency before investment growth appears• Economic concentration and workforce characteristics strengthen regional capital inflows• Threshold behavior confirms delayed investor response to institutional improvement KeywordsRegional Investment; Corruption Prevention; Agglomeration; Human Capital; Labor Force Participation